IMPLEMENTASI EVALUASI AUTENTIK PADA PEMBELAJARAN SKI KELAS VII DI MTS DARUN NAJAH BANYUWANGI - Fathi Hidayah; Bey Arifin Sidon; Annisa Kalimatul Hasanah (Tarbiyatuna Kajian Pendidikan Islam, 2022)
The countless problems in education have an impact on the transformation from the KTSP to the Curriculum 2013 (K13), so the evaluation standard is one of the standards that has been improved. The purpose of this study is to describe how authentic evaluation is used in class VII SKI learning, the different types of authentic evaluation, and the motivating and impeding factors for doing so. The researcher in this instance employs a descriptive qualitative methodology. Techniques for gathering data include observation, interviews, and documentation. The results are then reduced, the data is displayed, and conclusions are drawn and verified. Furthermore, use source triangulation techniques to verify the accuracy of the data. According to the study's findings, there have been three stages to the process of authentic evaluation activities in class VII SKI learning: planning, implementation, and evaluation. The teacher sets up a grid, creates questions, and creates answer keys during the planning phase. The teacher evaluated the students' affective, cognitive, and psychomotor skills at the time of implementation. Formative, summative, and portfolio evaluation are the three types of evaluation that are used. Both internal and external factors can act as supportive or inhibiting factors.